1998
DOI: 10.1038/bjc.1998.438
|View full text |Cite
|
Sign up to set email alerts
|

Phase II and pharmacokinetic study of paclitaxel therapy for unresectable hepatocellular carcinoma patients

Abstract: Major treatment toxicities (grade 3-4) were neutropenia (25%), thrombocytopenia (15%), infection (10%) and allergy (10%). Treatment-related deaths occurred in two patients. The median survival was 12 weeks (range 1-36). Paditaxel is metabolized by the liver and the pharmacokinetcs of paclitaxel in cancer patients with liver involvement or impairment may be important clinicalty. Pharmacokinetic study was completed in 13 HCC patients. The pacitaxel area under the curve was significantly increased (P < 0.02), cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(64 citation statements)
references
References 21 publications
3
57
1
3
Order By: Relevance
“…[3][4][5] Sorafenib is a multikinase inhibitor of the vascular endothelial growth factor receptor, platelet-derived growth factor receptor, and Raf. It is the only agent that has been shown to improve overall survival and to be well tolerated in subjects with advanced-stage HCC with well-preserved liver function.…”
mentioning
confidence: 99%
“…[3][4][5] Sorafenib is a multikinase inhibitor of the vascular endothelial growth factor receptor, platelet-derived growth factor receptor, and Raf. It is the only agent that has been shown to improve overall survival and to be well tolerated in subjects with advanced-stage HCC with well-preserved liver function.…”
mentioning
confidence: 99%
“…Taxol, one of the antimicrotubule chemotherapeutic drugs, has been reported to be effective in the treatment of many tumours including ovarian, breast and lung cancers (Chabner, 1991;Rowinsky and Donehower, 1991;Slichenmyer and Von Hoff, 1991) but not in HCC (Chao et al, 1998). The well-established action mechanism of Taxol in the treatment of cancer is based on stabilisation of microtubules in tumour cells and induction of apoptosis.…”
mentioning
confidence: 99%
“…In addition, several signal transduction pathways such as Raf, JNK (Torres and Horwitz, 1998;Wang et al, 2000) and specific cell cycle phase (Lin et al, 1998) have been indicated to be involved in Taxol-elicited apoptotic responses. Moreover, expression of oncogenes or drug resistance factors as well as decoy receptors induction could account for the low response rate after chemotherapy in patients with HCC (Chao et al, 1998;Yamanaka et al, 2000), including Taxol treatment.…”
mentioning
confidence: 99%
“…New chemotherapeutic drugs, such as paclitaxel, raltrexed, irinotecan, and nolatrexed, have not demonstrated encouraging results. These new drugs exhibit some antitumor activity, but response rates rarely exceed 10% (Rougier et al, 1997;Chao et al, 1998;O'Reilly et al, 1998;Stuart et al, 1999). The possible explanations for the refractioness of HCC to chemotherapy include tumor heterogeneity (Dexter and Leith, 1986), inadequate dosage of anticancer agents (Lai et al, 1990) and the inducible overexpression of the multidrug resistance gene (Huang et al, 1992).…”
Section: Discussionmentioning
confidence: 99%